Effect of Cassava Bioethanol By-Products and Crude Palm Oil Feeding on Fatty Acid Composition of Beef Meat and Fat in Crossbred Thai Indigenous Heifers - Chirasak Phoemchalard; Ronnachai Prommachat; Tanom Tathong; Suthipong Uriyapongson (Animals)
The quality and nutritional value of meat are significantly attributed to the composition of fatty acids (FAs). This investigation used gas chromatography to assess FAs in longissimus et lumborum (LL), semimembranosus (SM), and subcutaneous fat (SC) tissues of 18 heifers feeding low (15%, LCEP) or high (30%, HCEP) cassava bioethanol by-products (CEP) and 0 (CPO-0), 2 (CPO-2), or 4% (CPO-4) crude palm oil (CPO). The experimental diet was provided at 1.75% of body weight, along with free access to rice straw and water for 150 days. The results showed that the highest content of saturated (SFAs, 50.14, 42.76, and 68.76%, mainly C16:0), monounsaturated (MUFAs, 44.89, 49.14, and 30.41%, mainly C18:1n9c), and polyunsaturated fatty acids (PUFAs, 4.96, 8.10, and 0.84%, mainly C18:2n6c and C18:2n6t) were observed in LL, SM, and fat tissues. CPO supplementation significantly affected the FAs in LL and SM meat, with CPO-2 and CPO-4 diets leading to decreased SFAs and increased MUFAs and PUFAs compared to the CPO-0 diet. Multivariate analysis showed the most important FAs that highlight discrimination between different oil supplementation levels (CPO-0 vs. CPO-2, CPO-0 vs. CPO-4, CPO-2 vs. CPO-4) in LL (C18:2n6c, C20:3n3, C13:0), SM (C13:0, C18:0, C13:0), and SC fat (C18:2n6t, none, none) tissues. This data generates key insights into FA profiles resulting from different levels of oil supplements in cattle diets, which could influence future research on precision nutrition in beef production.